An optimized resistive CNT-based gas sensor with a novel configuration by top electrical contact - Zandi, Ashkan; Gilani, Ali; Ghafoori fard, Hassan; Koohsorkhi, Javad (Diamond and related materials, 2019)
The paper proposes a new fabrication method of a resistive gas sensor made of vertically aligned carbon nanotubes (CNT) by the perforated electrode. This new configuration can be also utilized with vertically aligned nanomaterial such as ZnO wires. This method contains two aspects, which are getting top electrical contact from MWCNTs and devising hexagonal pattern holes on the sensor surface to ease the gas flow through the sensor. Reaching ambient molecules to these dense CNT forests is always of the essence; also, the top electrical contact of the CNTs is a fabrication challenge. The high sensitivity of proposed CNT-based sensor is attributed to their collective large porous surface along with etched circular holes located at the apexes and center of a hexagonal pattern on sensor top contact. For optimal sensor performance, the simulation approach by ANSYS-FLUENT software has optimized circular holes diameters and distances. The fabrication process proposes an oxygenated plasma treated CNTs with top electrical contact devised by a certain simple method for the very first time. Top electrical contact has been fabricated possible by the procedure of immersing the CNTs in viscosity liquid and providing electrical contact using conductive paste. Well-aligned multi-walled carbon nanotubes (MWCNT) have been grown on glass substrate placed into DC-PECVD unit bearing approximately temperature of 350 °C. In this paper, the resistivity of carbon nanotubes at different temperatures for the ambient gas and linear sensitivity to oxygen gas has been investigated. The sensors with larger diameter nanotubes are more sensitive. Etching patterned holes with 200 μm diameter enhances the sensitivity up to 50%. [Display omitted]